Learning Based on Multicultural Values in Forming Students' Tolerant Character Through Citizenship Education - Mastura, Sinta Bella; Purwowidodo, Agus (Jurnal Ilmiah Iqra', 2024)
Learning Based on Multicultural Values in Forming Students' Tolerant Character Through Citizenship Education. Efforts to welcome a Golden Indonesia 2045 require the formation of good character from the young generation. Developing an attitude of religious moderation is one way that can be taken to create a generation that can compete on the world stage. Developing an attitude of religious moderation requires teachers' assistance, so teachers must be more innovative and creative in the learning process. This research aims to explain the role of teachers in fostering an attitude of religious moderation to face the challenges of an increasingly complex world. The research method used is a qualitative research approach that explores in-depth information. The location of this research was MI Manba'ul 'Ulum Buntaran. Data analysis was carried out using a data condensation model, which was carried out with data collection, data presentation, and conclusion. This research shows that MI Manba'ul 'Ulum students already know the concept of religious moderation in general. In practice, religious moderation has been implemented in this madrasah. Students carry out the application of an attitude of religious moderation through the habit of praying Duha, the habit of reading Surah Al-Waqi'ah every morning, P5 learning, personal approaches to students, studies delivered by preachers, the habit of always teaching an attitude of apology after making mistakes, and provide basic understandings of all religions in Indonesia.